THE EFFECT OF PESTICIDES ON ISOENZYME SPECTRUM OF CEREAL AND POTATO ANTIOXIDANT ENZYMES. - Manadilova, A.M.; Tursunova, A.K.; Utarbayeva , A.Sh. (Eurasian Journal of Applied Biotechnology, 2014)
The effect of herbicides (Glyphosate, Granstar) and fungicides (Tilt, Fundasol) on the isoenzyme profile of principal antioxidant enzymes: superoxidedismutase, catalase and peroxidase, was studied. Pesticides are related to nonspecific compounds that act after plants are grown and widely used to destroy pest both on agricultural and non-agricultural lands. Pesticides are commonly used when general control over vegetation is required. Pesticides get into plants mostly through green parts but may be absorbed by soil colloids and furthertakenin through plant roots. It is shown that the treatment of wheat and potato plants with pesticides (Granstar, Glifosat, Fundazol, Tilt) does not significantly impact thechange of isoenzyme spectrum of superoxide dismutase and catalase. More sensitivity to pesticide treatment was demonstrated by peroxidase. The treatment of wheat plants with Tilt and Glifosat (24 hours) results in the induced synthesis of new peroxidase isoforms. The analysis of obtained results and studied literature allows to conclude that the studied enzymes-antioxidants (superoxide dismutase, catalase and soluble peroxidase) can adaptively change their activity under the influence of pesticides. At that,for oxygen metabolism maintained at optimum level, the plant organism cells use several ways to adapt to changing conditions. Among them are change of some physical and chemical properties of enzyme-antioxidants, change of their isoenzyme spectrums and change of biosynthesis and disintegration speed of SOD, CAT and PO. It allows assuming that all the enzymes being studied may apparently be related to stress-specific enzymes,particularly soluble peroxidase.